1982
DOI: 10.3386/w0965
|View full text |Cite
|
Sign up to set email alerts
|

Government Debt and Private Leverage: An Extension of the Miller Theorem

Abstract: This paper shows how government financing decisions can influence the corporate decision to use debt or equity finance. In particular, it is shown that an increase in the stock of taxable government debt reduces the equilibrium quantity of corporate debt, and that an increase in the stock of tax-free government debt reduces the equilibrium quantity of corporate equity. The effects of inflation rate and tax rate changes are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…First, our results are consistent with government deficit financing crowding out corporate debt financing through competition for investor funds (Friedman, 1986). Second, and closely related, market imperfections, such as taxes (McDonald, 1983), informational frictions (Greenwood, Hanson, and Stein, 2010), and transaction costs (Krishnamurthy and Vissing-Jørgensen, 2012) generate an imperfectly elastic demand curve for corporate debt, as investors are no longer able to costlessly transform return streams from corporations to match their consumption needs. Consequently, fluctuations in the supply of government debt, a substitute for corporate debt, can shift the demand curve for corporate debt in a manner that affects equilibrium quantities.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…First, our results are consistent with government deficit financing crowding out corporate debt financing through competition for investor funds (Friedman, 1986). Second, and closely related, market imperfections, such as taxes (McDonald, 1983), informational frictions (Greenwood, Hanson, and Stein, 2010), and transaction costs (Krishnamurthy and Vissing-Jørgensen, 2012) generate an imperfectly elastic demand curve for corporate debt, as investors are no longer able to costlessly transform return streams from corporations to match their consumption needs. Consequently, fluctuations in the supply of government debt, a substitute for corporate debt, can shift the demand curve for corporate debt in a manner that affects equilibrium quantities.…”
Section: Introductionsupporting
confidence: 74%
“…Fluctuations in the supply of competing securities shift the demand curve for corporate debt in the opposite direction. One such substitute receiving significant theoretical attention is government bonds (e.g., Taggart, 1985;McDonald, 1983;Friedman, 1986). During the last century, government debt experienced several notable transitions, beginning with a dramatic expansion to fund World War II.…”
Section: Graphical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors of capital structure studies reported that the share of debt in company financing is stable in the long term (Sametz, 1964;Wright, 2004;frank & Goyal, 2008) or showed a different degree of debt increase in the post-war period (Miller, 1977;Taggart, 1985;McDonald, 1983). Gordon and Malkiel (1981), Philippon (2012), Strebulaev andYang (2013), andDeAngelo andRoll (2014) demonstrated that the debt level of US companies had increased in the second half of the 20 th century, while the proportion of organisations with relatively low debt had declined.…”
Section: Long-term Capital Structure Of Enterprises -Literature Reviewmentioning
confidence: 99%
“…My discussion of municipal debt in the Miller Model draws heavily on Auerbach andKing (1983) andMcDonald (1983).…”
Section: Discussionmentioning
confidence: 99%